Evaluasi Usability Dan Rekomendasi Perbaikan Tampilan Website Seleksi Mahasiswa (SELMA) Universitas Brawijaya - Qurrata Aynayya; Mochamad Chandra Saputra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Brawijaya University as one of the public universities in Indonesia, has a Seleksi Mahasiswa (SELMA) UB which used as a public official media for information delivery. Based on the result data from the initial questionnaire distributed to respondents, several shortcomings are occured on the SELMA UB website. Respondents are having difficulties in finding the required information, the ambiguous content layout on the website, unappealing website appearance, dysfunctional links, and the disturbing excessive scrolling features. Therefore, further evaluation is necessary to determine the usability and quality level of website services from the user's point of view. This study aims to improve the usability and quality value of website services by providing a recommendation scheme for website interface design. The evaluation result for SELMA UB website usability, measured using WEBUSE, shows 11 statement indicators with Moderate usability value which required improvements. Meanwhile, the evaluation result for quality of service by using WEBQUAL 4.0 and calculation of Importance Performance Analysis (IPA), shows the results of gap analysis between performance and importance is -0.78 or <0. For quadrant analysis results, there are 10 statement indicators in quadrant I, III, IV and in need of improvement. The outcome of the website interface design improvement recommendation based on the HHS Usability Guidelines is a website interface design mockup of SELMA UB.